Neuron-Derived Neurotrophic Factor Ameliorates Adverse Cardiac Remodeling After Experimental Myocardial Infarction. (March 2015) - Joki, Yusuke; Ohashi, Koji; Yuasa, Daisuke; Shibata, Rei; Kataoka, Yoshiyuki; Kambara, Takahiro; Uemura, Yusuke; Matsuo, Kazuhiro; Hayakawa, Satoko; Hiramatsu-Ito, Mizuho; Kanemura, Noriyoshi; Ito, Masanori; et al.
Abstract : Background—: Myocardial infarction (MI) is one of the major causes of death worldwide. Chronic heart failure is a serious complication of MI that leads to poor prognosis. We recently found that neuron-derived neurotrophic factor (NDNF) is a proangiogenic secretory protein that is upregulated in ischemic skeletal muscle. Here, we examined whether NDNF modulates cardiac remodeling in response to chronic ischemia. Methods and Results—: C57BL/6J wild-type mice were subjected to the permanent ligation of the left anterior descending coronary artery to create MI. Adenoviral vectors expressing NDNF or β-galactosidase (control) were intramuscularly injected into mice 3 days before permanent left anterior descending coronary artery ligation. Intramuscular administration of adenoviral vectors expressing NDNF to mice resulted in increased levels of circulating NDNF. Adenoviral vectors expressing NDNF administration improved left ventricular systolic dysfunction and dilatation after MI surgery. Moreover, adenoviral vectors expressing NDNF enhanced capillary formation and reduced cardiomyocyte apoptosis and hypertrophy in the post-MI hearts. Treatment of cultured cardiomyocytes with recombinant NDNF protein led to reduced apoptosis under conditions of hypoxia. NDNF also promoted the phosphorylation of Akt and focal adhesion kinase in cardiomyocytes. Blockade of focal adhesion kinase activation blocked the stimulatory effects of NDNF on cardiomyocyte survival and Akt phosphorylation. Similarly, treatment of cultured endothelial cells with NDNF protein led to enhancement of network formation and Akt phosphorylation, which was diminished by focal adhesion kinase inhibition. Conclusions—: These data suggest that NDNF ameliorates adverse myocardial remodeling after MI by its abilities to enhance myocyte survival and angiogenesis in the heart through focal adhesion kinase/Akt-dependent mechanisms. Abstract : Supplemental Digital Content is available in the text.